DARI SUTET MENUJU TEOLOGI BERBASIS EKOLOGI (TINJAUAN HADIS-HADIS PELESTARIAN LINGKUNGAN, KESEHATAN, DAN LAYANAN PUBLIK - Munawir Munawir (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2014)
This is the discussion about SUTET and the problems surrounding, whichare the environmental conservation and public service. Through the study of many related hadis, found that  environmental conservation and public service are basic value in Islam. These piety (environmental conservation and public service) are the integral part from human’s piety to God. Being religious is not only about being good to God, but also to universe. Then by this spirit created a theology concept on ecology basic. Key Words: Environmental Conservation, Public Service, Piety